Legal Protection For Doctors In Providing Medical Services - Steavanno, Dedet; Nurdin, Boy; Fakrulloh, Zudan Arief (Interdiciplinary Journal and Hummanity (INJURITY), 2023)
The rampant was reported in the mass media mass related to the doctor's profession, that many malpractices were found by doctors in Indonesia and according to the report of the central health legal aid institution, there were approximately 150 cases of malpractice even though most did not reach the court. Likewise, public reports to the Indonesian Doctors Association (IDI) from 1998 to 2004 were 306 cases of complaints of alleged malpractice. This condition causes anxiety or concerns among doctors, because if it does not help it is declared wrong according to law and when helped at risk, the patient or family is prosecuted if it is not in accordance with his expectations. Because of that, in addition to the obligations that must be met, doctors are also equipped with doctors' rights. Normatively these rights have been listed in the legislation which can be demanded its existence, especially regulated in Article 50 of the UUPK.